Mothers of angels: (re)living the death of the child as a coping strategy - Larissa Gramazio Soares; Élida Kuchla; Verônica de Azevedo Mazza; Letícia Gramazio Soares; Maria Isabel Raimondo Ferraz; Aline Padilha Mattei (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To describe the experiences lived by mothers facing the death of their children. Method: A qualitative, exploratory and descriptive research conducted in Guarapuava-PR, with six participants of the "Marias" group that brings together mothers who lost their children and share their experiences to spontaneously help other women in the process of mourning. Data collection took place from May to August 2017, through a focus group. The speeches were organized by the Iramuteq® software and analyzed according to Creswell. Results: Age ranged from 28 to 40 years old, and most participants were married and catholic. The categories express the need to strengthen bonds and to create ways in which women can express themselves; the importance of the social network to accommodate mourning; the relevance of ethical and humanized care; and group identity as an element to promote resilience. Conclusion and Implications for practice: Describing the potentialities and weaknesses in the process of loss and grief enables a qualifying and humanizing care, overcoming care gaps, stimulating the creation of creative and dialogical spaces in maternal care. These results may guide the professional approach by considering the sociocultural context and the risk factors experienced by the mothers, by supporting the development of resilient skills and enabling a humanized and individualized care.